A bánsági horvátok néhány etnikai-társadalmi jellemzője és sajátossága - Kókai, Sándor (Közép-Európai Közlemények, 2013)
The different groups of the Banatian Croats arrived in the area between the Maros River and the Lower Danube in four waves over a three-hundred-year-long period. The oldest Croatian settlers in the Banat are called ‘Krašovani’ by the Serbs. According to tradition, they arrived from Bosnia during the 16th century. The second group lives to the east of Timisoara, whose ancestors, called Šokci, resettled from the Banat in the 17th century. The third group is made up of Croats originating from the counties of Lika and Bodrus, who moved to the riversides of the Lower Danube and the Timis in the Banat and became the residents of the Banatian settlements of Perlasz, Opáva, Sztarcsova, Borcsa, Galagonyás and Omlód along the military frontier. These settlers were Šokci using the ‘Šokac dialect’. The fourth group contained settlers speaking the Kajkavian dialect who arrived in the Banat at the beginning of the 1800s between the Bega and the Timis River. They were the vassals of the archbishop of Zagreb, since during the establishment of the military frontier near Karlovac the archbishop conveyed his lands along the Kulpa River and received Banatian settlements in return, where some of the vassals settled down. The fifth group of settlements resided by the Croats emerged in 1803, when residents of three settlements on the karst around Carawova settled down in Károlyfalva and Királykegye.